Keadilan Hukum Dalam Putusan Perceraian Narapidana Perspektif Critical Legal Studies - Daulay, Royyan Mahmuda Al’Arisyi; Shinta Dewi Rismawati; Maghfur Ahmad (Restorative : Journal of Indonesian Probation and Parole System, 2023)
Divorce is the right of every married couple in Indonesia to the extent of the reasons written in the marriage law. Prisoners are citizens who are given a criminal sentence in prison for a specified period of time. In a divorce trial involving a prisoner, often the judge's decision will be in the form of a verstek decision. This type of decision is made because convicts cannot attend court proceedings due to limitations in prison. This research assesses legal justice from the perspective of critical legal studies in viewing prisoners' divorce decisions in the form of verstek decisions. The research method used is juridical-normative research with a descriptive analytical approach. Data collection techniques were carried out using literature study methods that were relevant to the research object. The results of the research show that critical legal studies views that the verstek decision in prisoner divorce cases does not reflect the value of legal justice, only legal certainty. The recommendation is that efforts are needed to present post-modern regulations with values of justice, benefit and legal certainty, especially regarding the issue of prisoner divorce. Abstrak Perceraian merupakan hak setiap pasangan di Indonesia sesuai dengan alasan yang tertulis dalam undang-undang perkawinan. Narapidana merupakan warga negara yang diberikan hukuman pidana di dalam penjara untuk kurun waktu yang ditentukan. Apabila terjadi perceraian yang melibatkan narapidana, seringkali keputusan hakim akan berupa putusan verstek. Keputusan sedemikian dibuat karena narapidana tidak bisa menghadiri proses persidangan di pengadilan akibat keterbatasan di penjara. Penelitian ini menilai keadilan hukum perspektif critical legal studies dalam memandang putusan perceraian narapidana yang berupa putusan verstek. Metode penelitian yang digunakan adalah penelitian yuridis-normatif dengan pendekatan deskriptif-analitis. Teknik pengumpulan data dilakukan dengan metode studi literatur yang relevan dengan objek penelitian. Hasil penelitian menunjukkan bahwa critical legal studies memandang putusan verstek kasus perceraian narapidana tidak mencerminkan nilai keadilan hukum, baru sekadar kepastian hukum saja. Rekomendasinya adalah perlu upaya untuk menghadirkan regulasi yang bersifat post-modern dengan nilai-nilai berkeadilan, berkemanfaatan, dan kepastian hukum, terutama dalam persoalan perceraian narapidana. Keywords: Cerai Gugat, Narapidana dan Studi Hukum Kritis, Putusan Verstek